Entrepreneurship in China: a review of the role of normative documents in China’s legal framework for encouraging entrepreneurship - Kenneth-Southworth, Ernest; Watters, Casey; Gu, Chuning (Centre for Strategic and International Entrepreneurship, Krakow, Poland, 2018)
The objective of the article is to provide an overview of the Chinese legal framework while examining the laws and legal provisions influencing entrepreneurship in China for both Chinese and foreigners, arguing that the current legal environment encourages domestic entrepreneurship and foreign investment. Research Design & Methods: This article explores the legal environment for entrepreneurship in China by taking a comparative and normative approach to introducing several recent initiatives established through normative documents. Findings: As China seeks to transform from an export economy towards a domestic consumption model, the government is increasing implementing initiatives to encourage domestic entrepreneurship. The majority of these initiatives are established through normative documents that, while not technically defined as law, nevertheless have legal effect. Implications & Recommendations: It argues that the legal framework is principally targeted at domestic entrepreneurship but has also benefited foreign entrepreneurship. Contribution & Value Added: This article is unique in that it explores the role of normative documents in Chinese initiatives to encourage entrepreneurship. In conclusion, China has invested heavily both economically and legally in the encouragement of entrepreneurship and in the cooperation between domestic and foreign entrepreneurs.